QRS voltage of the electrocardiogram and Frank vectorcardiogram in relation to ventricular volume. Issue 10 (October 1977) - Talbot, S; Kilpatrick, D; Jonathan, A; Raphael, M J
Abstract : Left ventricular volumes were estimated in 59 patients, who were investigated by single plane ventriculography and coronary arteriography. The relation of the left ventricular end-diastolic volumes to the QRS voltage of the 12-lead electrocardiograms and Frank vectorcardiograms was examined. It was found that the maximum spatial QRS voltage and the R wave voltage of leads V5 and V6 in patients without left ventricular hypertrophy were inversely correlated with end-diastolic volume. This inverse relation of QRS voltage and left ventricular volume may explain loss of QRS voltage with dilatation of the heart. In patients with left ventricular hypertropy QRS voltage is usually positively correlated with the degree of hypertrophy, but there is no significant correlation in the presence of cardiac dilatation. If the results of this study are extrapolated to patients with left ventricular hypertrophy and cardiac dilatation, then the inverse correlation of volume and QRS voltage may reduce the diagnostic sensitivity of unipolar chest lead and vectorcardiographic criteria of left ventricular hypertrophy.